Climate change, water balance and energy efficiency in some seasons in Colombia [Cambio climático, balance hídrico y eficiencia energética en algunas estaciones climáticas en Colombia] (2016)
The purpose of this paper is to compare the water balance and energy efficiency in the seasons analyzed by the students of the first cohort of PhD in sustainable development at the University of Manizales in the module called climate change, water and energy efficiency. In the case of water balances a correlation of the components of supply and demand is used, which are analyzed throughout a significance test to verify the relationship between variables. Regarding the issue of energy efficiency the tradeoff between water consumption as the production of biofuels and the reduction of CO2 emissions that it produces are evaluated. Subsequently the results shown by this exercise are explained and finally some alternatives are presented as an action plans if any of the presented case happens.